Development of Soft Wrinkled Micropatterns on the Surface of 3D-Printed Hydrogel-Based Scaffolds via High-Resolution Digital Light Processing - Mauricio A. Sarabia-Vallejos; Scarleth Romero De la Fuente; Nicolás A. Cohn-Inostroza; Claudio A. Terraza; Juan Rodríguez-Hernández; Carmen M. González-Henríquez (Gels)
The preparation of sophisticated hierarchically structured and cytocompatible hydrogel scaffolds is presented. For this purpose, a photosensitive resin was developed, printability was evaluated, and the optimal conditions for 3D printing were investigated. The design and fabrication by additive manufacturing of tailor-made porous scaffolds were combined with the formation of surface wrinkled micropatterns. This enabled the combination of micrometer-sized channels (100–200 microns) with microstructured wrinkled surfaces (1–3 μm wavelength). The internal pore structure was found to play a critical role in the mechanical properties. More precisely, the TPMS structure with a zero local curvature appears to be an excellent candidate for maintaining its mechanical resistance to compression stress, thus retaining its structural integrity upon large uniaxial deformations up to 70%. Finally, the washing conditions selected enabled us to produce noncytotoxic materials, as evidenced by experiments using AlamarBlue to follow the metabolic activity of the cells.